Development of the Petroleum Refining in the Republic of Côte D'ivoire- Primary Processing of Refining - Adiko, Serge-B.; R.A, Kemalov (International Journal of Engineering and Technology, 2018)
The article is considering the technology of primary processing of S. I. R (Societe Ivoirienne de Raffinage). General modern technology of petroleum refiningThe problems with primary processing technologies of refining and ability development of the petroleum refining in the Republic of Côte d'Ivoire. Comparison of the two types of technologies (primary of refining) between SIR for Cote d’ivoire and general technology in Russia.S. I. R (Societe Ivoirienne de Raffinage) is the only petroleum refinery in the Republic of ivory coastThe Republic of Côte d'ivoire is located in West Africa with a population of 22.8 million (data for 2014 b is the second economic power in sub-region (West Africa) after Nigeria, with an average of 8% of GDP over the last five years, Economic development of the country and its economic development is related to petroleum production and refining in the Republic of Côte d'ivoire.Refining is the obvious economic rate for a more diversified and more competitive economy